Electronic Field Trips for Science Engagement: The Streaming Science Model - Jamie Loizzo; Mary J. Harner; Deborah J Weitzenkamp; Kevin Kent (Journal of Applied Communications, 2019)
While institutions of higher education work to engage PK-12 youth in STEM (science, technology, engineering, and mathematics) concepts and careers via in-person programming, PK-12 teachers and students face many logistical and access constraints for physically traveling to sites off of school grounds during the school day. Throughout the years, electronic field trips (EFTs) have offered a digital way for schools to engage in meaningful ways with museums, parks, laboratories, and field research sites. In order for EFTs to be effective, they should be cost effective and created collaboratively with teachers, students, subject matter experts, and instructional design and communication professionals. Streaming Science is an online science communication platform that aimed to develop and implement an effective EFT model. Three Streaming Science live interactive EFTs webcasted online were piloted from various locations during 2017-2019 to test wireless internet connections, mobile technologies, STEM content, and impacts on students’ interest, attitudes, and learning. The model proved iPads and mobile applications in the field for web streaming were effective for connecting scientists with school audiences. In this professional development article, authors describe the Streaming Science EFT model, including recommendations for instructional design, the pre-production process, content development, teacher collaboration, student engagement, mobile hardware and software, and assessment.
Keywords: Science; STEM; mobile; electronic field trip; science communication; online engagement; distance education; Streaming Science